Detection of tea concentration macerated onto the artificial teeth using fiber optic displacement sensor - Yasin, M.; Harun, Sulaiman Wadi; Apsari, R.; Suhariningsih, -; Kusminarto, -; Karyono, -; Ahmad, Harith (National Institute of Optoelectronics, 2010)
The performance of fiber-optic displacement sensor, which uses artificial teeth as a target is demonstrated for various tea concentration macerated onto the target. In the experiment, a concentric type of bundled fiber and yellow He-Ne laser are used as a probe and a light source, respectively. The location of peak voltage shifts to a shorter displacement as the tea concentration increases. The sensitivity of both slopes are also reduced with the increment of tea concentration. This is attributed to the reduction of the received light intensity because of the change of the refractive index at the teeth surface, which actually changes the angle of the reflected light beam. The stability of the sensor, a high sensitivity and the simplicity of the design, low cost of fabrication make it suitable for chemical, biomedical, pharmaceutical and process control applications.